Evaluasi Penataan Pedagang Kaki Lima Pada PasarTradisional (Studi Kasus Pasar Tradisional - Edito Dwi Antoro (MAJALAH TEKNIK SIMES, 2022)
The existence of PKL Pasar Panorama can also create jobs, while on the other hand the existence of street vendors who are not taken into account in spatial planning has become a burden for the city. Street vendors have a negative impact on the urban structure, while on the community the existence of street vendors in addition to having a negative impact also provides benefits/positive impacts on the community. This study was conducted to determine the impact of street vendors on the panoramic market of Bengkulu city that sells in the green zone (pavements and road bodies) and to find out the wishes of street vendors in the research location.Data analysis is a stage to determine the problems faced. The analytical techniques used in this study are as follows: Descriptive Analysis(Descriptive analysis is an analysis that aims to provide a description (description) of a data, such as the average, the amount of variance, the minimum and maximum values, and so on.) and SWOT analysis (SWOT matrix analysis can be formulated various possible strategies in the development of attractiveness. The combination of SWOT components is a strategy that supports the development of potential objects and attractions such as: Strengths Opportunities (SO) Strategies, Strengths Threats (ST), Weaknesses Opportunities (WO) and Weaknesses Threats (WT)).Research result is: The existence of street vendors can create jobs, while on the other hand the existence of street vendors who are not taken into account in spatial planning has become a burden for the city. Street vendors are active in the public spaces of the city without heeding the public interest, resulting in a change in the function of the space, The problem of street vendors is a problem in the lives of many people that is never finished from time to time. To overcome the negative impacts caused by the existence of street vendors, a unity of understanding is needed between the government and the street vendors themselves, Street vendors are mostly practiced by people in Bengkulu City. Although not all of those who work in this sector are Bengkulu City residents, street vendors in their lives raise various urban environmental problems in Bengkulu City. The identified PKL desires include, among others, PKL wanting an official lapak, wanting a cheap retribution and wanting access to loan capital.